Aqueous extract of tiririca, bio-stimulant and micronutrient in beet productivity and quality parameters - Alves Neto, Alfredo José; Ritter, Giovana; Echer, Márcia de Moraes; Belmonte, Cristiani; Pires, Ely; Lorenzetti, Eloisa (Scientia Agraria Paranaensis, 2019)
The use of stimulants in the beet crop can serve as a complement in the production and quality of the final product. In order to compare and evaluate the effects of physiological activators and aqueous extracts of tiririca on the parameters of beet quality and productivity, an experiment was conducted at the field in the municipality of Formosa do Oeste (Paraná, Brazil), in a typical dystroferric RED LATOSOL. The experimental design was randomized blocks, with four treatments (T1 - control, T2 - Stimulate® 0.004%, T3 - tiririca (Cyperus rotundus L.) 10%, T4 - Starter® 0.004%), with seven replicates. The seedlings were kept in the soil for 24 h in each treatment and then taken to the field and planted in beds. Leaf height (cm), number of leaves, stem length (cm), root diameter (cm), slight effects (%), serious effects (%) and productivity (t ha-1) were evaluated. Micronutrient application increased yields by around 5 t ha-1. The aqueous extract of tiririca and biostimulant presented a larger root diameter in the beet.